Statistical analysis of the nexus between dietary habits and practices with clinical outcome in Saudi patients with type 2 diabetes - Sami, Waqas (2019)
Dietary habits and sedentary lifestyle are the major factors for rapidly-rising incidence of Diabetes Mellitus (DM) in the Kingdom of Saudi Arabia (KSA). At this rapid rate of increase in the number of Saudi diabetics, it is expected that by the year 2022 the prevalence of T2DM would be 44.1%. Diabetes complications, especially Diabetic Retinopathy (DR) is also increasing at an alarming pace in KSA. In 2007, the prevalence of DR was 31% which in 2015 increased to 36.4%. It was observed that almost in every quarter-yearly around 30% - 40% of the diabetic patients were presenting in the clinics with dyslipidaemia, early end-organ complications and elevated HbA1c levels. It has been pointed out in the published literature that the relation between dietary habits and practices of type 2 diabetics have not been studied well in KSA. Moreover, diabetic dyslipidaemia and uncontrolled HbA1c is also on the rise in KSA with very few studies addressing this issue. In addition, there is a bleak evidence in the literature about the availability of dietary consultation model that can be used to carry out the dietary assessment of type 2 diabetics. Therefore, the objectives of this research were; to assess diabetic patient’s baseline Diabetes Mellitus Knowledge (DMK), Dietary Knowledge (DK), Dietary Attitude (DA), Dietary Practices (DP), lipid profile and HbA1c; to empirically test the hypothesised dietary consultation model and, to find the prevalence of DR and its association with HbA1c. Pre-test was conducted to evaluate the face validity and content validity, whereas, the purpose of pilot study was to evaluate the questionnaires’ reliability and validity. The data for main study was collected from 5th February to 24th April 2017 from 350 patients using systematic random sampling technique by direct investigation method. One-sample Wilcoxon signed ranked test, one-sample chi-square test, Mann-Whitney U test, Pearson chi-square, logistic regression and Partial Least Squares Structural Equation Modelling (SEM) was used to test the hypothesised relationships. Baseline analysis showed that type 2 diabetics had poor DMK and DK, inappropriate DA, unhealthy DP and uncontrolled lipid profile and HbA1c. Scores generated from baseline analysis were used in SEM. A formative model was used in this research. Results of outer model evaluation showed the evidence of convergent validity, no problem of multicollinearity, and outer weights of all indicators were significant as evident by t-values and p-values. Findings of structural model showed that there is a strength interrelationship between DMK, DK, DA, DP and HbA1c. Moreover, DMK (influential factor) was directly significantly predicting DK and DP, whereas, it had the highest significant indirect effect on HbA1c (outcome variable). The prevalence of DR was found to be 28.3% and had a significant association with HbA1c. There is great unawareness of healthy diet, poor eating habits and void of exercise-culture in Arab society. It breeds diabetes especially of type 2 and obesity. It demands a three-dimensional programme of promoting early age exercise and nutrition education irrespective of region, gender and stratum of society. The study proposed a validated dietary consultation model, this model can be used alone or integrated with any available diabetes consultation model for more effective diabetes care. Healthcare providers should pay special emphasis on diabetics DMK, DK and DA as these factors have a direct and indirect influence on DP and HbA1c. Findings of the overall proposed dietary consultation model facilitates a new healthcare paradigm. Conducting dietary assessment of diabetics at initial stage and periodically can help in overall reduction in diabetes complications, thus improving the quality of life of patients.